(untitled) (Bangladesh Journal of Botany, 2026)
The Erguna wetland in Inner Mongolia, China, represents Asia’s largest woody wetland and a critical stopover for migratory birds, yet it faces increasing biodiversity threats from conventional management practices focused mainly on greening rate while overlooking vertical vegetation structure. This study investigated the relationship between canopy structure and understory plant diversity across three canopy density groups in 30 standardized plots of Erguna National Wetland Park, integrating traditional Chinese garden principles with modern ecological assessment methods. Leaf area index and canopy openness were measured using hemispherical photography, while biodiversity was assessed by species richness, Shannon-Wiener index, and functional group composition. Results revealed significant gradient characteristics in canopy structure and microclimate conditions among the groups (P < 0.001). A unimodal relationship emerged, with moderate canopy closure (40-60%) supporting maximum diversity (R2 = 0.68, P < 0.001). Functional group analysis showed herbaceous plants and shrubs dominated at intermediate canopy density, while high leaf area index suppressed herbaceous species but favored mosses and ferns. Structural equation modeling demonstrated direct light-driven effects (β = 0.62) and indirect water regulation pathways (β = 0.35) governing understory diversity. Multi-layer canopies increased biodiversity by approximately 35% and enhanced soil water retention. These findings validate traditional Chinese principles of moderate density and provide actionable canopy management thresholds (LAI 2.5-3.5, openness 40-60%) for biodiversity-oriented wetland restoration. Bangladesh J. Bot. 55(1): 1-12, 2026 (March)